2003
DOI: 10.1073/pnas.0630531100
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of perenniality in rice and sorghum

Abstract: Annual and perennial habit are two major strategies by which grasses adapt to seasonal environmental change, and these distinguish cultivated cereals from their wild relatives. Rhizomatousness, a key trait contributing to perenniality, was investigated by using an F 2 population from a cross between cultivated rice (Oryza sativa) and its wild relative, Oryza longistaminata. Molecular mapping based on a complete simple sequence-repeat map revealed two dominant-complementary genes controlling rhizomatousness. Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(210 citation statements)
references
References 21 publications
9
200
0
1
Order By: Relevance
“…For example, increased planting density reduces tiller number and increased fertilizer treatment increases tiller number. Genetic studies show that perennialism is controlled by relatively few genes (Hu et al, 2003;Westerbergh and Doebley, 2004). The identification of these genes will be essential for understanding the regulation of branching in perennial grasses.…”
Section: The Role Of Hormones In the Regulation Of Rhizomes In Perennmentioning
confidence: 99%
“…For example, increased planting density reduces tiller number and increased fertilizer treatment increases tiller number. Genetic studies show that perennialism is controlled by relatively few genes (Hu et al, 2003;Westerbergh and Doebley, 2004). The identification of these genes will be essential for understanding the regulation of branching in perennial grasses.…”
Section: The Role Of Hormones In the Regulation Of Rhizomes In Perennmentioning
confidence: 99%
“…3). In an F 2 mapping population of O. sativa crossed with Oryza longistaminata, Hu et al (2003) have identified multiple QTL that correlate with the presence of rhizomes, which are often correlated with the perennial habit. Two of these loci overlap with similar loci in sorghum suggesting that a few major regulators control growth form in many species of grasses.…”
Section: Subfamily Ehrhartoideaementioning
confidence: 99%
“…Recently, Li et al (2006) reported that reduced shattering of the mature inflorescence associated with rice domestication was caused in part by human selection of an amino acid substitution in the DNAbinding domain of the sh4 gene. Rhz2 and Rhz3 might be targets for such macro-mutations affecting rhizomatousness (Hu et al, 2003). However, little is known on the fate of many genes involved in the molecular pathway after the genotype has lost the ability of rhizomatousness.…”
Section: Introductionmentioning
confidence: 99%
“…The Sorghum genus has become a model for dissecting the molecular control of rhizomatousness (Paterson et al, 1995;Hu et al, 2003;Jang et al, 2006). S. halepense L. Pers.…”
Section: Introductionmentioning
confidence: 99%